The university and the teaching training in Brazil: brands and contradictions - Canan, Silvia Regina; Sudbrack, Edite Maria (Revista Complutense de Educación, 2019)
The aim of this article is to provoke a discussion regarding the issue of the contradictions that surround university and teacher training in Brazil, trying to understand the contradictions of the historical process of constitution of the Brazilian university. The problematization is involved in an agenda of discussions on policies for higher education and intervention of international organizations. This is a review on the state of the art through a theoretical study, anchored to studies developed by the Nucleus of studies and research in policies and processes of higher education (Neppes). It points out the different brands that were part of the constitution of higher education in Brazil and the centrality that has dominated it, through a model of university that caters preferentially to private interests. These have occupied the gaps that were leaving institutions and public policies, transforming the universities into lucrative business desks, culminating in the loss of their autonomy. In this way, universities begin to develop research that satisfies the market. Thus, it is questioned: Is it possible to go beyond this mercantilist model? This is the challenge and the main question that we seek to answer in this work.